Entrepreneurial Competencies and Strategic Behavior: a Study of Micro Entrepreneurs in an Emerging Country - Gustavo Behling; Fernando César Lenzi (BBR: Brazilian Business Review)
The purpose of this paper is to analyze the relationship between the entrepreneurial competencies and the strategic behavior patterns of entrepreneurs in response to the social and economic environment in which they operate, taking into consideration limitations that are common to emerging countries. The study takes a quantitative approach with a survey of 211 Individual Micro Entrepreneurs (IME) operating in the Brazilian state of Santa Catarina. The results demonstrated that there were differences between mean scores for the entrepreneurial competencies when compared across the entrepreneurs’ strategic behavior types. Moreover, entrepreneurs who were Reactors possessed a mean of 6 out of the ten entrepreneurial competencies, Defenders had 7.97, Analyzers had 8.38, and Prospectors had 8.56. The paper reveals which competencies are most likely to be associated with each strategic behavior type. The findings also indicate that entrepreneurial competencies can impact the adoption of more consistent business strategies, contributing to actions that respond to unstable social and economic scenarios.